Stress investigation for crack problems in fiber-reinforced composite materials - Yeo, Leonard Zi Ping (2017)
In the current project, two main types of crack problems in fiber-reinforced composite materials: cracks due to inclusion-matrix interface debonding and cracks due to matrix cracking, are investigated. The theory of Fracture Mechanics, both Linear Elastic and Elastic Plastic, is used for the stress analysis in the composite models under uniaxial loading condition. The Finite Element Method was used to produce numerical results for the various types of crack problems. The first physical problem solved is the interface crack; an arc crack along a circular inclusion/matrix interface (two-phase model) whereby debonding occurs. A study on the impact of the half-debonding angle and shear modulus ratio on the arc crack has been performed in detail to determine the various fracture parameters (Stress Intensity Factors, J-Integrals, Plastic Zone Size). Both the mode I and mode II Stress Intensity Factors are studied but more emphasis is placed on the mode I for the comparison as it is a more common form of loading. The second problem investigated is the matrix cracking; a straight crack in a pure matrix surrounded by various inclusions. This problem is solved with the aid of three-phase composite model. The influence of the fiber volume concentration, shear modulus and crack orientation angle on the plastic zone size and J-integrals are studied in detail. The shielding effect, determined by the shear modulus ratio of the inclusion to the matrix, has been analysed for both problems. The purpose is to investigate whether the inclusion phase will retard or promote crack propagation.